Managing Urban Growth in Sub-Saharan Africa - Mabojunye, Akin L. (World Bank, Washington, DC, 2012)
This article addresses the problems of governance in municipalities in Africa. The concern has been to adapt traditional systems of governance to the needs of modern urban management. This article investigates the need for a new analysis of the twin problems of urban land and urban management in sub-Saharan Africa. This need is based on the apparent paradox between the dynamic, city-creating activities of civil societies in all of these countries, and the weak capabilities of states to guide and direct these activities. This article focuses on governance at the community level, where empowerment and accountability begin. It argues that a prerequisite for dealing with these problems is an institutional environment with which the target populace is familiar and to which it is likely to relate in participating in managing the city. The importance of the particularly dynamic systems of traditional governance at the lowest level in managing urban growth is only recently being recognized.